Charity in the formation and development of the education system in the Terek region (1861–1917) - A. V. Politova (Гуманитарные и юридические исследования)
The article discusses certain aspects of the history of Russian charity in the Terek region. The author analyzes the sources on this topic and offers an extensive historiographic review and monographic literature. The researcher refers to the history of charity in the southern Russian province. The period from the moment of the abolition of serfdom to the Russian revolution of 1917 is one of the most dynamic in Russian history, which could not but affect the development of charity. This period became a historical challenge for the multi-ethnic Terek region, which turned out to be one of the most economically backward territories. The integration of the Caucasian territories into the socio-cultural space of Russia was inevitably accompanied by the need to pull up the outskirts to the socio-economic and cultural level of the central territories. Charity has become one of the social practices that began to develop during this period in the territory of the Terek region. The author used archival documents to study the charitable activities of both the Slavic and the mountain population of the Terek region. For the first time, unpublished documents are introduced into scientific circulation, which help to reconstruct the history of the activities of individual societies. The article explored the private financial component of charitable activities, studied the institutional component. In particular, it is shown how informational support was provided by the newspaper «Terskiye Vedomosti». Given the multinational composition of the study area, the author made the efforts of local ethnic elites to increase the literacy level of their peoples a separate aspect of the study.